Psychoanalytic Treatment of Psychological Addiction to Alcohol (Alcohol Abuse) - Johnson, Brian (Frontiers in Psychology, 2011)
Abstract The DSM-V Committee plans to abolish the distinction between Alcohol Abuse and Alcohol Dependence (DSM5.org). The author presents a case report as a proof of concept that this distinction should be retained. The author has asserted that Alcohol Abuse is a purely psychological addiction, while Alcohol Dependence involves capture of the ventral tegmental dopaminergic SEEKING system (Johnson 2003). In psychological addiction the brain can be assumed to function normally, and ordinary psychoanalytic technique can be followed. For the patient described, transference interpretation was the fundamental key to recovery. Alcoholic drinking functioned to prevent this man from remembering overwhelming childhood events; events that were also lived out in his current relationships. Murders that occurred when he was a child were hidden in a screen memory. The patient had an obsessional style of relating where almost all feeling was left out of his associations. After he stopped drinking compulsively, he continued to work compulsively. The maternal transference had to be enacted and then interpreted in order for overwhelming memories to be allowed into conscious thought. After psychoanalysis, the patient resumed drinking and worked a normal schedule that allowed more fulfilling relationships. He had no further symptoms of distress from drinking over a 9 year followup.